ANALISIS KESULITAN SISWA KELAS XI SMK DALAM MENYELESAIKAN MASALAH PROGRAM LINEAR MENGGUNAKAN BLENDED LEARNING - Jamal Thahir Karo Karo (Universitas Muhammadiyah Surabaya, 2022)
this study aims to describe the difficulties students experience in resolving linear programs, describing the various student difficulties, describing the student's level of difficulty and describing the factors that cause the student's greatest difficulty by using blended learning. The study USES qualitative descriptive methods. The subject of this study is the xi class of 37 students on a land-terrain flight center that suffers from linear program materials. Data collection is obtained by way of observation, diagnostic tests of linear program materials, angkets and interviews with students. Research results are student difficulties as well as the factors that cause difficulties students experience in linear program materials. As for the difficulties students experience is 15.2 percent concept difficulties, principle difficulties of 38.4%, difficulty in solving problems of 193%. Certain difficulties of the subject amount to 27.1%. The underlying factor is the internal factor of learners with low student interest, and the external factor of most influential learners in families and schools.Â Keywords: Difficulty, linear programming, problem solving, blended learning